Diversity and life-forms of a woody-herbaceous community on the quartzite rocky complexes in the Brazilian Iron Quadrangle - Silva, Wesley Alves (2019)
Although campos rupestres are iconic rock outcrops with a high biogeographic value in Brazilian highlands, little is known about the drivers responsible for the plant community pattern. We studied the diversity and life forms of the woody and herbaceous components occurring along different phytophysiognomies of the quartzite rocky complexes in highlands of the Quadrangle, Minas Gerais State, Brazil. A total of 130 plots were allocated in three phytophysiognomies along the pedogeomorphological gradient: i) herbaceous campo rupestre; ii) upper and lower strata of montane forest (capão florestal) and iii) scrub. Overall, 4 446 individuals were sampled, distributed among 218 species, especially from families: Asteraceae, in general; Myrtaceae, in the woody community; and Poaceae and Cyperaceae, in the herbaceous community. Species diversity, life forms, and abundance showed differences between phytophysiognomies. The most frequent life form was phanerophyte (montane forest and scrub), followed by hemicryptophyte (herbaceous campo rupestre). Our study reveals marked differences in the floristic composition, species richness, and life form spectrum among phytophysiognomies on a local scale. Such differences probably indicate that there is a high environmental heterogeneity at a small spatial scale.